GAMBARAN PENGETAHUAN DAN SIKAP IBU TENTANG KEKERASAN SEKSUAL PADA ANAK TK ‘AISYIYAH 24 KOTA PADANG TAHUN 2024 - Armalena; Ningsih, Agusiah Fajar; Meta Rikandi (Section Editor) (Jurnal Kesehatan Lentera 'Aisyiyah, 2024)
Sexual violence is any act that uses violence, pressure, manipulation, or threats to force another person to perform unwanted or violating sexual acts. The initial survey found that 5 mothers did not know about violence and 1 mother knew about sexual violence. This research aims to determine the description of mothers' knowledge and attitudes regarding sexual violence among children at Kindergarten 'Aisyiyah 24 Padang in 2024. This type of research is quantitative with a descriptive design. This research was conducted at Kindergarten 'Aisyiyah 24 Padang which was carried out on July 22 to August 2, 2024. The sample of this study was mothers who had kindergarten children, with a total of 35 respondents. The sampling technique was total sampling and used univariate analysis. The results of the study showed that almost half (43%) of respondents had insufficient knowledge and almost all (80%) of respondents had good attitudes about sexual violence against children at TK 'Aisyiyah 24, Padang city in 2024.It is hoped that schools can provide education about sexual violence against children in preventing cases of sexual violence against children.